PID- Based Stabilization of a One- DOF Educational Aero-Pendulum - Evangelista, Jessica Pereira de Souza Xavier; Mendes, André Luis Carvalho; Brandão, Alexandre S. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This work presents the development and experimental validation of a low-cost didactic platform based on a one-degree-of-freedom aero-pendulum controlled by a PID (Proportional-Integral-Derivative) controller. The platform was designed to support control systems education by enabling students to apply theoretical concepts in a real, nonlinear, and unstable system. The experimental setup includes a DC motor with PWM actuation, an angle sensor for feedback, and an Arduino Nano for controller implementation. A graphical interface developed in MATLAB App Designer was also employed for real-time visualization and data analysis. The controller was evaluated under classical input signals such as step, ramp, and sinusoidal references. Results demonstrate that the PID controller is capable of stabilizing the system with acceptable transient and steady-state performance. A comparative study of different gain configurations highlights the importance of proper tuning for system robustness, reinforcing the value of using physical platforms to enhance practical learning, conceptual understanding, and controller design skills in engineering education.